Women's parliamentary representation in 27 western democracies : cultural, socio-economic and political obstacles to entry - Gardiner, Frances Katherine (Trinity College (Dublin, Ireland). Department of Political Science, 2000)
This study examines obstacles to women's parliamentary representation in 27 western democracies. Women’s political underrepresentation internationally is a cause of concern to international organisations such as the UN, Inter-parliamentary Union, the Council of Europe and the EU, who commission research, publish reports and urge national governments to acknowledge and address the democratic deficit in their legislatures. Women's workforce participation has long been associated with increased interest and participation in political matters. However, despite growing educational and employment opportunity over the past two decades, women's parliamentary participation continues to lag, and in 1999 stands at 13 percent, just over half-way to holding a quarter of parliamentary seats.
Keywords: Politics, Ph.D.; Ph.D. Trinity College Dublin